Improving Vocational School Student’s Autonomous by Using E-Module Based on Predict Observe Explain (POE) - Agung Winarno; Sofia Hinggit (Universitas Negeri Malang, 2022)
The development of science and technology encourages the education sector in Indonesia to continue to innovate in learning activities. Teachers are required to be innovative and creative in creating an attractive learning environment. This study aims to produce an e-module product based on Predict Observe Explain (POE), determine the feasibility level of an e-module based on Predict Observe Explain (POE), and determine the level of student learning independence. This study adapted the Borg and Gall research steps by simplifying it into seven research steps. The e-module feasibility test was carried out by module experts and content experts. Product trials were carried out on students of vocational high school taking Office Automation Major in Archives Management subjects. The results showed that the e-module product developed was declared valid or feasible to be used as a student learning resource, and the results of the student product trial provided interesting criteria and made it easier to understand the material, the learning outcome test resulted in very high learning autonomy criteria. Keywords: E-module, learning autonomy, predict observe explain, vocational school